Analysis of Al2O3 layers morphology and microstructure - Skoneczny, W. (Фізико-хімічна механіка матеріалів, 2010)
The paper presents the characterization of obtaining Al2O3 oxide layers on aluminium AlMg2 alloy as a result of hard anodizing by the electrolytic method in a three-component electrolyte. The Al2O3 layers obtained on the AlMg2 alloy in the three-component SBS electrolyte were subjected to detailed microstructural investigations (by means of a scanning electron microscope, SEM). By applying X-ray diffraction, examination of the obtained oxide layers phase compositions was carried out. It was found that the Al2O3 oxide layers obtained via hard anodizing in a three-component electrolyte are amorphous. The chemical composition of the Al2O3 layers is presented and compared to the results of stechiometric calculations for the Al2O3 layer. Surface morphologies of the obtained oxide layers are characterized and discussed in nano- and microscopic scales. The surface morphologies of the layers obtained have a significant influence on their properties, including their susceptibility to further modification (e.g. to incorporation of graphite), their wear resistance and the capacity for sorption of lubricants. Описано спосіб отримання оксидних покривів на основі Al2O3, сформованих на підкладці сплаву AlMg2 анодуванням у трикомпонентному електроліті. Мікроструктурні особливості шарів Al2O3 досліджено за допомогою сканівного електронного мікроскопа (SEM). Для вивчення фазового складу покривів використовували рентгенодифракційний аналіз. Виявлено, що оксидні покриви з Al2O3, отримані анодним оксидуванням у трикомпонентному електроліті, аморфні. Подано хімічний склад покривів та порівняно його з результатами стехіометричних обчислень. Проаналізовано морфологію поверхні оксидних покривів та обговорено їх поведінку на нано- та макрорівнях. Морфологія поверхні суттєво змінює інші властивості, зокрема, їх здатність до подальшої модифікації (включення графіту), зносотривкість та схильність до сорбції компонентів мастил. Описан способ получения оксидных покрытий на основе Al2O3, сформированных на подкладке сплава AlMg2 анодированием в трехкомпонентном электролите. Микроструктурные особенности слоев Al2O3 исследовано с помощью сканирующего электронного микроскопа (SEM). Для изучения фазового состава покрытий использован рентгенодифракионный анализ. Обнаружено, что оксидные покрытия из Al2O3, полученные анодным оксидированием в трехкомпонентном электролите, аморфны. Наведен химический состав покрытий и сравнено его с результатами стехиометрических расчетов. Проанализирована морфология поверхности оксидынх покрытий и обсуждено их поведение на нано- и макроуровнях. Морфология поверхности существенно изменяет другие свойства, в частности, их способность к дальнейшей модификации (включения графита), износостойкость и склонность к сорбции компонентов масла.